Kemerdekaan dan Kemandirian Mahkamah Agung dan Mahkamah Konstitusi Dalam Kekuasan Kehakiman - -, Sugiaryo - (Joglo, 2011)
ABSTRACT Universal principles of judiciary authority freedom covers such as personal independence, substantive independence, internal independence and institution independence as well. As it`s seen from normative dimension the freedom and independence of supreme court and constitution court as the ruler of judiciary authority in Indonesia has been in line with the universal principles of judiciary authority. As it`s seen from empirical dimension, freedom and independence of supreme court and constitution court as the ruler of judiciary authority hasn`t be done consistenthy. Keywords : freedom and independence of supreme court and constitution court, judiciary authority.